Changes Anxiety in Patients Preoperative Abdominal Surgery After Giving a Combination of Benson Relaxation and Dhikr - Rahmawati, Rizky; Hartono; Sunarto (Future Science, 2024)
Background: Surgery is a medical procedure that aims to save lives and prevent disability by making an incision in the part of the body to be repaired. One type of major surgery is abdominal surgery. Surgery can cause a psychological response in patients. Anxiety is a psychological response that usually occurs in preoperative abdominal surgery patients. One of the ways to handle anxiety is with non-pharmacological techniques in the form of the Benson and Dhikr methods. Objective: To determine the effect of the combination of the Benson and Dhikr methods on anxiety levels in preoperative abdominal surgery patients at RSUD Dr. Moewardi Surakarta. Methods: This study used a pre-experimental research type with a one-group pretest-posttest design. The sample of this study consisted of 32 preoperative abdominal surgery patients with anxiety at RSUD Dr. Moewardi Surakarta. Sampling technique with purposive sampling. Results: After carrying out the Wilcoxon Signed Rank Test, the results obtained a significance of 0,000 (p-value<0,05). Conclusions: There is a combined effect of the Benson and Dhikr methods on the level of anxiety in preoperative abdominal surgery patients at RSUD Dr. Moewardi Surakarta.